PENGARUH TAX AVOIDANCE, DIVIDEND POLICY, DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN - Govindo, Gabriela Giselin; Jonathan, Aries (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The increasing level of business competition in Indonesia causes every company to try to develop its firm value. One of which is through capital which can be obtained by selling shares. Firm value is an important influencing factor for making investment decisions because investors will pay attention to how well the company's performance is. This research was conducted with the aim of obtaining empirical evidence regarding the influence of the independent variables dividend policy, investment decision, leverage, profitability, firm size, liquidity, institutional ownership, and tax avoidance. The object of this research uses a population of all consumers non-cyclicals and consumer cyclicals sector companies listed on the Indonesia Stock Exchange (BEI) from 2020 to 2022. Sample selection was carried out using a purposive sampling method. Data analysis uses multiple linear regression. The data that passed the sample selection criteria was 33 company data out of a total of 99 company data. The testing results indicate that profitability and leverage influence firm value. A high level of leverage makes the company able to maximize its operational activities to obtain high profits so that it becomes a positive signal for investors and increases firm value. A high profitability serves as a signal that the company has good growth prospects in the future so that investors will be more interested in investing and contributing to an increase in the firm value. However, dividend policy, investment decision, firm size, liquidity, institutional ownership, and tax avoidance show no significant influence on firm value